Binders alternative to Portland cement and waste management for sustainable construction—part 1. Issue 3 (July 2018) - Coppola, Luigi; Bellezze, Tiziano; Belli, Alberto; Bignozzi, Maria Chiara; Bolzoni, Fabio; Brenna, Andrea; Cabrini, Marina; Candamano, Sebastiano; Cappai, Marta; Caputo, Domenico; Carsana, Maddalena; Casnedi, Ludovica; et al.
This review presents "a state of the art" report on sustainability in construction materials. The authors propose different solutions to make the concrete industry more environmentally friendly in order to reduce greenhouse gases emissions and consumption of non-renewable resources. Part 1—the present paper—focuses on the use of binders alternative to Portland cement, including sulfoaluminate cements, alkali-activated materials, and geopolymers. Part 2 will be dedicated to traditional Portland-free binders and waste management and recycling in mortar and concrete production.